2022
DOI: 10.3390/ma15030995
|View full text |Cite
|
Sign up to set email alerts
|

Creation of 3D Model of Stainless-Steel Billet’s Grain after Three-High Screw Rolling

Abstract: The three-high screw rolling of AISI 321 billet from 60 mm to 52 mm diameter was performed using an MISIS-100T mill. When screw rolling was carried out, a set of sections were made in the billet’s cross-section at the stationary stage of screw rolling. SolidWorks was applied to make the 3D model of the rolled billet’s grain using microstructure images. The same technique was applied for the creation of the 3D model of a nondeformed billet’s grain. A comparison of the 3D models’ shape and dimensions before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Nevertheless, the hardness change patterns observed as a result of the present research have been identified for other screw rolling temperature and deformation regimes and for other materials, such as titanium alloy [30], steels [29,31], nickel alloy [32] and magnesium alloy [33]. Microstructure twist, as illustrated in Figure 10b,c, was identified for the three-high screw rolling of commercial pure aluminum billet at completely different temperatures from the current study temperature and deformation regimes [36], three-high screw rolling of AISI 1020 steel billet [37], and of AISI 321 steel billet [36]. These data indicate that stress-strain influences the microstructure and hardness formation substantially (independently form the regimes and rolled billet material), and its effect should be one of the key issues for examination in future research into screw rolling and RSR processes.…”
Section: Resultsmentioning
confidence: 63%
“…Nevertheless, the hardness change patterns observed as a result of the present research have been identified for other screw rolling temperature and deformation regimes and for other materials, such as titanium alloy [30], steels [29,31], nickel alloy [32] and magnesium alloy [33]. Microstructure twist, as illustrated in Figure 10b,c, was identified for the three-high screw rolling of commercial pure aluminum billet at completely different temperatures from the current study temperature and deformation regimes [36], three-high screw rolling of AISI 1020 steel billet [37], and of AISI 321 steel billet [36]. These data indicate that stress-strain influences the microstructure and hardness formation substantially (independently form the regimes and rolled billet material), and its effect should be one of the key issues for examination in future research into screw rolling and RSR processes.…”
Section: Resultsmentioning
confidence: 63%
“…However, at present, the precise expressions for the temperature dependence of elastic moduli are not known for all materials. Therefore, most authors continue to use the Sellars expression in the form (2), in this case calling the quantity Q the "apparent" activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…Austenitic stainless steels are widely used in the chemical industry, thermal and nuclear power, and medical and cryogenic engineering [1]. The production process of semi-finished products and final products from these steels usually includes the stage of hot deformation via rolling, forging, or extrusion [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to develop a technique to estimate the size of this neutral layer using both the stress-strain state and the kinematic parameters' distribution along with the microstructure features. It is also relevant that the RSR parameters directly influence the microstructure, considering the results in [44,45].…”
Section: Introductionmentioning
confidence: 99%